The Effect of Side Barriers on Road Performance Levels (A Case Study: Pasar Cigasong, Majalengka) - Teguh Puji Setiawan; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2025)
The impact of side barriers on road service levels is a crucial consideration in urban transportation planning and management. Side barriers refer to various roadside activities that disrupt traffic flow, such as market operations, illegal parking, and pedestrian movement. In busy urban areas like the vicinity of Pasar Cigasong in Majalengka, these activities can significantly hinder the smooth flow of traffic. Traffic congestion often arises from such disruptions, making it essential to understand their effects. This study aims to assess how side barriers affect road service levels at Pasar Cigasong in Majalengka. The research methodology includes gathering data on side barriers, vehicle speeds, and traffic volumes. The results are expected to offer a thorough understanding of traffic conditions around the market and highlight the main factors contributing to traffic issues. The research was conducted in the Pasar Cigasong area, situated in an urban environment close to the city center of Majalengka Regency. The analysis found that the road service levels at the three-terminal intersection and Pasar Cigasong primarily fall within the average to high range. Based on these findings, the author suggests that the local government take proactive measures to address the growing traffic volumes and prevent future congestion.